Using live streams to share knowledge – a diagnosis - Fonseca, Leonardo Mariano Gravina; Barbosa, Simone Diniz Junqueira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Several studies indicate that live stream is an emerging research topic in Human-Computer Interaction. Although live streams for entertainment are the most popular kind, there are also knowledge sharing live streams (KSLS). Embrapa, a Brazilian public agricultural research company, uses this kind of tool to disseminate its research results to the public, which is distributed in an extensive geographic territory. The objective of this work is to make a diagnosis through an online questionnaire with the public of an Embrapa broadcast, identifying their profile and preferences, as well as possibilities for improvements in KSLS. This study’s research questions are: Has the live stream proved to be an efficient tool for sharing knowledge? What are the user’s preferences? Is it possible to improve their experience? Our results indicate that live streams have great potential for sharing knowledge. In accordance with current studies, we have recognized that great effort is needed to engage the public and there are opportunities to design and develop resources to improve the broadcast environment. In particular, users who participated in our study were interested in annotations and screen recording tools, surveys to influence the offered content, and interactions through multiple-choice questions. We also present some lessons learned regarding preferences, habits, and characteristics of the users.